Kualitas Sumber Daya Manusia Dalam Menyelesaikan Berkas Tagihan Di Sekretariat Daerah Kabupaten Minahasa Utara Bagian Umum - WINOWODA, TIRZA; TULUSAN, FEMMY (JURNAL ADMINISTRASI PUBLIK, 2023)
The problem with human resources actually lies in the skills or abilities that exist in a person. Most civil servants do not master their own work which shows a poor work ethic, besides that they cannot make their own decisions, and lack self-discipline. This directly shows their quality as private employees who are paid by the community and the state, but are of poor quality. If the office recruits characters like this, the result will only lead to inefficiencies, complicated problems, and decreased productivity. This study aims to find out how the Quality of Human Resources is in Completing Billing Files at the Regional Secretariat of the General Section. The method used is a qualitative approach. By type of case study. The use of this method is to explore data as detailed as possible until the data obtained is saturated. This study used in-depth interviews, observation and documentation from the field for data collection methods. This research found that civil servants understand their respective job parts through the training they attended, besides that experience during education is also useful in completing billing files. even so there are still obstacles that arise such as system and network errors and then the completeness of documents and the accuracy of documents often hinders the process of completing billing files. Interestingly, this study found something new from the determination and seriousness of civil servants, namely that employees often work overtime until midnight to complete bills that are hampered due to existing constraints. This research provides input in the future to continue research with the theme of Quality of Human Resources. This study suggests the Regional Secretariat of North Minahasa Regency to involve more civil servants in technical guidance so that the knowledge gained can increase the productivity of completing invoices.